2008
DOI: 10.1038/sj.bjc.6604422
|View full text |Cite
|
Sign up to set email alerts
|

Common dysregulation of Wnt/Frizzled receptor elements in human hepatocellular carcinoma

Abstract: Dysregulation of growth factors and their receptors is central to human hepatocellular carcinoma (HCC). We previously demonstrated that the Frizzled-7 membrane receptor mediating the Wnt signalling can activate the b-catenin pathway and promotes malignancy in human hepatitis B virus-related HCCs. Expression patterns of all the 10 Frizzled receptors, and their extracellular soluble autoparacrine regulators (19 Wnt activators and 4 sFRP inhibitors) were assessed by real-time RT -PCR in 62 human HCC of different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
167
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(176 citation statements)
references
References 39 publications
3
167
0
1
Order By: Relevance
“…Furthermore, three other Wnt genes (Wnt3, Wnt4 and Wnt5A), and three FZD genes (FZD3, FZD6 and FZD7) are also upregulated in HCC tissues and preneoplastic peritumoural tissues as compared with normal liver tissues, suggesting that their overexpression may be an early event in hepatocarcinogenesis. However, only the overexpression of FZD7 has been associated with nuclear and/or cytoplasmic accumulation of β-catenin in HCC [70][71][72] .…”
Section: Wnt and Fzdmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, three other Wnt genes (Wnt3, Wnt4 and Wnt5A), and three FZD genes (FZD3, FZD6 and FZD7) are also upregulated in HCC tissues and preneoplastic peritumoural tissues as compared with normal liver tissues, suggesting that their overexpression may be an early event in hepatocarcinogenesis. However, only the overexpression of FZD7 has been associated with nuclear and/or cytoplasmic accumulation of β-catenin in HCC [70][71][72] .…”
Section: Wnt and Fzdmentioning
confidence: 99%
“…The TCF/LEF family has several spliced forms with unknown functional significance and it is suggested that they may activate preferential genes [86] . In HCC, mutations of TCF-4 are rare with 315 August 10, 2011|Volume 2|Issue 8| WJCO|www.wjgnet.com [70][71][72] phospho-GSK3β High 52 IHC [73] Axin1 Low 67 IHC [76] Dvl High 71 Western blotting [82] Prickle-1 Low 55 PCR [82] HDPR1 Low 58 PCR [83] PIN1 High 53 Western blotting [65] TCF-4 High 91 PCR [87] LEF-1 High 52 IHC [88] CDH17 High 72 IHC [90] CDH17: Cadherin-17; Dvl: Dishevelled; FZD: Frizzled; phospho-GSK3β: Phosphorylated glycogen synthase kinase 3β; HDPR1: Human homologue of Dapper; IHC: Immunohistochemistry; LEF: Lymphoid enhancer factor; PCR: Polymerase chain reaction; PIN1: Peptidyl-prolyl cis/trans isomerase; TCF: T-cell factor.…”
Section: Tcf/lefmentioning
confidence: 99%
“…First, we focused on Fz3, as it was expressed in HCC cell lines consistently according to a previous report (15). To investigate the role of Fz3 in cell proliferation, we transfected PLC/PRF/5, HLE, Huh-6 and HeLa cells with Fz3-siRNA.…”
Section: Resultsmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) arises in liver of Fz7 transgenic mice (13). Fz3, Fz6 and Fz7 genes are upregulated in HCC tissues, compared with surrounding nontumor tissues (14,15). However, because Fz3, Fz6 and Fz7 are expressed in surrounding non-tumor tissues, their clinically mediated inhibition may give rise to adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that canonical Wnt signaling pathway is over-activated through FZD7 receptor in many cancers including colorectal, hepatocellular carcinoma (HCC), triple negative breast cancer (TNBC), esophageal cancer, gastric cancer, and Wilm's tumor cell (25)(26)(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%